Profile of primary blood current infections in a neonatal intensive care unit (Research, Society and Development, 2022)
Objective: To evaluate the profile of Primary Bloodstream Infections in a Neonatal Intensive Care Unit. Method: Exploratory and cross-sectional study, carried out in the Neonatal Intensive Care Unit of a reference maternity hospital in Piauí. The sample consisted of all reported cases of primary laboratory bloodstream infection and primary clinical bloodstream infection from January to December 2019. Results: The most frequent healthcare-related infections were primary laboratory bloodstream infection (54.78%) and primary clinical bloodstream infection. At the beginning of the year 2019, there was an increase in the global density (48.5) in relation to the median of 2018 (28), which declined throughout the year, reaching the end of the same with a global density lower than the median (25, 6). The main bacteria isolated in blood cultures were coagulase negative Staphylococcus (229) and klebisiella pneumoniae (52). Regarding the resistance profile, the negative coagulase Staphylococcus showed 75% resistance to Oxacillin. For Staphylococcus aureus, resistance to Oxacillin dropped to almost half of the samples (48.1%). In gram-negative bacteria, the main agents were Klebsiellas, with a resistance profile for Piperacillin-Tazobactam of 28.3%. Conclusion: Primary laboratory bloodstream infections and primary clinical bloodstream infections represent the main topographies of infections in neonatal ICUs, as well as the microbiological profile is similar to the profile of neonatal infections found in the literature.